Weather - Thompson, Philip Duncan; O'Brien, Robert; Time-Life Books (Time-Life International : Amsterdam, 1971)
Text and pictures explain the ingredients and phenomena of weather and the art of forecasting it.
Includes index.
Bibliography: p. 196.
1
Keywords: Weather